SLC25A51 is a mammalian mitochondrial NAD+ transporter - Luongo, Timothy; Eller, Jared M.; Lu, Mu-Jie; Niere, Marc; Raith, Fabio; Perry, Caroline; Bornstein, Marc R.; Oliphint, Paul; Wang, Lin; McReynolds, Melanie R.; Migaud, Marie E.; Rabinowitz, Joshua D.; et al. (Nature, 2020)
Mitochondria require nicotinamide adenine dinucleotide (NAD+) to carry out the fundamental processes that fuel respiration and mediate cellular energy transduction. Mitochondrial NAD+ transporters have been identified in yeast and plants1,2, but their existence in mammals remains controversial3-5. Here we demonstrate that mammalian mitochondria can take up intact NAD+, and identify SLC25A51 (also known as MCART1)—an essential6,7 mitochondrial protein of previously unknown function—as a mammalian mitochondrial NAD+ transporter. Loss of SLC25A51 decreases mitochondrial—but not whole-cell—NAD+ content, impairs mitochondrial respiration, and blocks the uptake of NAD+ into isolated mitochondria. Conversely, overexpression of SLC25A51 or SLC25A52 (a nearly identical paralogue of SLC25A51) increases mitochondrial NAD+ levels and restores NAD+ uptake into yeast mitochondria lacking endogenous NAD+ transporters. Together, these findings identify SLC25A51 as a mammalian transporter capable of importing NAD+ into mitochondria.
Im Titel ist das Pluszeichen hochgestellt
Gesehen am 20.10.2025